Effect of balanced nutrition intervention based on local food on young women of orang rimbo in Bukit Duabelas National Park, Jambi province - Asparian Asparian; Sri Asturi Siregar; Usi Lanita (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The prevalence of anemia in Indonesian teenagers is still high, namely 32%, or more than 6,000 Indonesian teenagers suffered from anemia. Long-term anemia has an impact during pregnancy, thus affecting the health of the mother and baby. The population of the Anak Dalam Tribe in Jambi Province is 200 thousand people who still live in the forests and around the TNBD forests at risk of experiencing malnutrition, including their teenage daughters, due to socio-economic status factors, limited access to health services, food security, family empowerment, and low levels of knowledge and education. . The research analyzed the effect of local food-based balanced nutrition interventions on Orang Rimbo adolescent girls. Quasi Experimental Design, totaling 70 people. The research results showed that there was significan relationship between dominan food sources consumed (p-value = 0.000) and the type of local food consumed (p-value = 0.007) with balanced nutrition (BMI), as well as the influence of interventions carried out in food processing among young women of the Orang Rimbo people in TNBD (p-value = 0.000). It was concluded that there was an influence of interventions carried out in food processing on young women of the Orang Rimbo people in Bukit Duabelas National Park.